2021
DOI: 10.28945/4755
|View full text |Cite
|
Sign up to set email alerts
|

Doctoral Candidates’ Academic Writing Output and Strategies: Navigating the Challenges of Academic Writing During a Global Health Crisis

Abstract: Aim/Purpose: To date, few studies have investigated the impact of global health crises on the academic writing of doctoral candidates. This paper seeks to start a conversation about the impact of the ongoing COVID-19 pandemic on doctoral candidates’ academic writing output and strategies. Background: This paper employs and analyses data elicited from surveys and interviews involving doctoral candidates from around the world. Data were collected during April 2020, at a time when government-mandated lockdowns a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 66 publications
2
4
0
2
Order By: Relevance
“…Finally, while not included in the SEM, based on these correlations, lockdown may be linked to both the health and research domains. Overall, these results are consistent with several works that found that the COVID-19 lockdown negatively impacted the doctoral experience regarding work and research (Cahusac de Caux, 2021;Covington & Jordan, 2022) and mental health (Evans et al, 2021). Moreover, during a one-year longitudinal study conducted in France, Paucsik et al (2022) discovered that doctoral students' stress, anxiety, and depression levels increased during COVID-19.…”
Section: The Hypotheses Of Th E Study and Th E Corresponding Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Finally, while not included in the SEM, based on these correlations, lockdown may be linked to both the health and research domains. Overall, these results are consistent with several works that found that the COVID-19 lockdown negatively impacted the doctoral experience regarding work and research (Cahusac de Caux, 2021;Covington & Jordan, 2022) and mental health (Evans et al, 2021). Moreover, during a one-year longitudinal study conducted in France, Paucsik et al (2022) discovered that doctoral students' stress, anxiety, and depression levels increased during COVID-19.…”
Section: The Hypotheses Of Th E Study and Th E Corresponding Resultssupporting
confidence: 90%
“…The students who intended to drop out were also particularly worried about their research work due to the lockdown during the pandemic compared to those who did not. The pandemic had negative consequences on the doctoral students' research work (Cahusac de Caux, 2021;Evans et al, 2021). This study's logistic regression model predicting dropout intention confirmed that research plays an important role in the intent to discontinue the doctoral program.…”
Section: Research Domainsupporting
confidence: 59%
“…Amongst international students, the language barrier is perceived as a conspicuous stress-producing issue that affects students' overall socio-academic experiences. That affects students' selfrespect (Benson, Barkhuizen, Bodycott, & Brown, 2012;Khalil, 2022) and also causes a hurdle to establishing relationship of friendships particularly with their host student, particularly with their host students particularly (Cahusac, 2021;Cowley & Ssekasi, 2018;Khalil, 2022;Khanal & Gaulee, 2019;Dewey, Bown, & Egget, 2012;Sverdlik, Hall, & McAlpine, 2020). Zaheer and Zia (2013) executed a study regarding thirteen abroad-qualified doctoral scholars in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…Brown and Aktas (2012) argued that there is a dearth of knowledge on the experiences of international Muslim students despite the acknowledgment that faith can influence a travel experience. Furthermore, mostly the research regarding international students' experiences is conducted in the context of North America though most of such research conducted in the UK and Australia reasonably resonates to some extent with the same results (Bista, 2016;Bista & Gaulee, 2017;Cahusac, 2021;Cowly & Ssekasi, 2018;Khalil, 2022;Khanal & Gaulee, 2019;Lee, 2010;Sverdlik, Hall, & McAlpine, 2020).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation